Large‐scale mass movements recorded in the sediments of Lake Hallstatt (Austria)–evidence for recurrent natural hazards at a UNESCO World Heritage site - Stefan Lauterbach; Michael Strasser; Kerstin Kowarik; Hans Reschreiter; Gerhard W. Mandl; Christoph Spötl; Birgit Plessen; Achim Brauer (Journal of Quaternary Science, 2023)
The Bronze to Iron Age underground salt mining complex of Hallstatt (Austria) is widely recognised for its cultural importance and wealth of archaeological artefacts. However, while the daily life in the salt mines is archaeologically well documented and environmental effects of the mining activity have been investigated recently, the impact of natural hazards on the prehistoric mining community is still poorly understood. For instance, while it is well established that the prehistoric underground mines have repeatedly been destroyed by large‐scale mass movements, only little is known about the characteristics and extent of these events as well as about mass‐movement recurrence during more recent times. To shed light on past mass‐movement activity in the vicinity of the Hallstatt salt mines, we investigated sediment cores from adjacent Lake Hallstatt. Within the regular lake sediments we identified three large‐scale event deposits, which are interpreted to originate from spontaneous or seismically induced mass movements in the mid‐19th and late 9th century ce and the mid‐4th century bce. While the age of the latter event is in good agreement with the abandonment of the famous Iron Age cemetery at Hallstatt, the younger events indicate that large‐scale mass movements also occurred repeatedly during the Common Era.